Whole-core transport solution via deterministic SN transport/p-CMFD overlapping local/global calculation in hexagonal geometry problem. (January 2015) - Yoo, Han Jong; Imron, Muhammad; Cho, Nam Zin
Highlights: Overlapping local/global (OLG) iteration method is extended to hexagonal geometry. The local solution is obtained by deterministic SN transport method. The local problems are embedded in the global p-CMFD equation solver. OLG iteration method reproduces whole-core transport solution within few iterations. Abstract: In this paper, the overlapping local/global (OLG) iteration method based on deterministic SN transport/p-CMFD calculations was extended to hexagonal core geometry. For this framework, a deterministic SN transport code and p-CMFD equation solver was implemented on triangular cell base. These two calculations are iteratively performed with proper boundary condition update until it reaches converged solution, which is then compared with the direct whole-core transport solution. Two variations from the original overlapping local/global iterative scheme are also introduced and tested: (1) zeroth local calculation of fixed-k problem type with initially guessed incoming angular flux and multiplication factor, and (2) local calculation with non-overlapping region (nonoverlapping local/global iteration). Several numerical test results show OLG system has been successfully implemented on hexagonal core geometry and its variations improve the computational efficiency.